Study on the ESS-VRB state of charge estimation - Lei, Yuze (2016)
There is a new type of Energy Storage System (ESS) named Vanadium Redox Battery (VRB) System, which can be used to solve some problems brought by the development of renewable energy. For instance, it shows a good potential for shaving power grid peak, smooth the fluctuation and improve the power quality. In addition,the vanadium redox battery system has been employed in large scale energy storage due to its high energy efficiency, long cycling life and a low cost. This dissertation presents an equivalent electrical circuit model to describe the charge characteristic of vanadium redox battery (VRB). The model neglect the effect of temperature on the battery performance for the simplicity. The state of charge (SOC) of VRB is an indication of how much energy is stored in the battery. It is very necessary to have the accurate SOC estimation of VRB in practical situation when the battery is employed to the power system. To make the battery’s state of charge estimation more accurate, this work proposed an online parameters identification algorithm for the VRB model. One of the VRB models is The Thevenin model which will be employed in this simulation. The Matlab/Simulink software will be employed to model the VRB battery and process the data with Recursive least squares methods. The estimation of SOC optimize the battery’s operation and management.